RESEARCH TRENDS IN SMALL AND MEDIUM ENTERPRISES AND ECONOMIC GROWTH: A BIBLIOMETRIC STUDY - Valdyan Drifanda; Kiromim Baroroh; Maimun Sholeh (STABILITY : Journal of Management and Business, 2025)
This study aims to conduct a bibliometric analysis of literature on Micro, Small, and Medium Enterprises (MSMEs) and economic growth. This study analyzes scientific publications indexed in the Scopus database for the period 2020-2025 to map publication trends, identify leading journals and authors, reveal collaboration patterns, analyze citation impact, and identify key research themes. The results show an increase in research activity in this field, with "Sustainability (Switzerland)" as the main source of publications. Authors such as Batara Surya and institutions such as Bosowa University have made significant contributions. A global collaboration network has been revealed, with China, the United Kingdom, Spain, South Africa, Pakistan, and Malaysia playing important connecting roles. An article by Myovella G (2020) had the highest global citation impact. Key research themes included "SMEs," "economic growth," "innovation," and "sustainability," indicating the evolution of research focus over time. This research provides comprehensive insights into research developments in the field of MSMEs and economic growth, as well as identifying opportunities for further research. The results of this study are expected to be useful for researchers, practitioners, and policymakers interested in MSME and economic growth issues.